Field Training and Level of Stress in College Students: A comparison between Nursing Students who take care of ill Children and Early Childhood Education Students who Take care of Healthy Children - Al- Momani, Siham M.; Abdu, Maram Fayez (Advances in Social Sciences Research Journal, 2018)
Background: The fact that clinical experiences and field training are stressful to nursing students specially the beginners student is well understood. Significant of the study: This study would provide useful insights for faculties, preceptors; nursing and early childhood students involved in field training, and the implications for education, further research, and training support could be replanned accordingly. Method: Participants were asked to sign a covering letter which explains the participants right and demographic data. Participants who submitted all the surveys numbered 40 out of 50 students in early childhood education, and 40 out of 56 nursing students at Al-Balqaa applied University. Almost all the students were female, between 19-22 years of age. Three longitudinal surveys were administered. Beck Depression Inventory Modified Arabic Version scale was used to measure stress level. Results: Overall stress level for both groups of students were high in the three round of surveys, more than one-third of the students were stressed before admitted to their assigned training fields two weeks after the training and at the end of the training period. The survey which was carried out after two weeks of training got the highest degree of stress level, clarified from the highest standard deviation of all surveys reading.